Prevalence and Correlates of Withdrawal-Related Insomnia among Adults with Alcohol Dependence: Results from a National Survey - Brower, Kirk J. (2010)
Insomnia during acute alcohol withdrawal (AWD) as well as persisting insomnia during post-acute withdrawal is associated with relapse. Rates of insomnia in clinical samples of alcohol-dependent patients range from 36 to 91%, but the prevalence of AWD-related insomnia in the general population is unknown. The purpose of this study was to describe the prevalence of insomnia as a symptom of acute AWD and its correlates in a general population of alcohol-dependent individuals. Data were analyzed from the 2001-2002 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), which sampled 43,093 adults. The prevalence of AWD-related insomnia among individuals with a lifetime diagnosis of alcohol dependence was 31.7%, which ranked fourth among the eight listed DSM-IV withdrawal symptoms. Among individuals that met lifetime criteria for both alcohol dependence and AWD, the prevalence of insomnia was approximately 50%. Lifetime diagnoses of major depression and drug use disorders were significant correlates of AWD-related insomnia in multivariate analyses. A less than one-year duration of the heaviest drinking period as well as the onset of alcohol dependence between ages 18 and 27 were negatively associated with AWD-related insomnia. AWD-related insomnia is a common symptom among alcohol-dependent adults in the general population and is related to lifetime co-occurring diagnoses, age at onset of alcohol dependence, and duration of heaviest drinking period. Its prevalence in the general population provides a representative base rate against which to compare the widely varying rates reported in clinical populations. Because of its relatively frequent prevalence and association with relapse, assessment and treatment of AWD-related insomnia should be routinely considered in clinical settings.